2022
DOI: 10.1093/genetics/iyac144
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic base substitution patterns in diverse species reveal links to cancer and metabolism

Abstract: Analyses of large-scale cancer sequencing data have revealed that mutagenic processes can create distinctive patterns of base substitutions, called mutational signatures. Interestingly, mutational patterns resembling some of these signatures can also be observed in normal cells. To determine whether similar patterns exist more generally, we analyzed large data sets of genetic variation, including mutations from seven model species and single nucleotide polymorphisms (SNPs) in 42 species, totalling >1.9 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…In the case of SBS5 and SBS40, the causes for both damage and repair are less clear. Recent experimental evidence suggests that one of the possible causes of SBS5 damage may be protonation of single-stranded DNA (ssDNA) [49, 50], while the formation of ssDNA is known to be increased in acute hypoxia [51]. Notably, these experimental studies also found that the source of the damaging protons may be glycolytic sugar metabolisation, which is strongly upregulated under hypoxic conditions [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of SBS5 and SBS40, the causes for both damage and repair are less clear. Recent experimental evidence suggests that one of the possible causes of SBS5 damage may be protonation of single-stranded DNA (ssDNA) [49, 50], while the formation of ssDNA is known to be increased in acute hypoxia [51]. Notably, these experimental studies also found that the source of the damaging protons may be glycolytic sugar metabolisation, which is strongly upregulated under hypoxic conditions [52].…”
Section: Resultsmentioning
confidence: 99%
“…This revealed novel associations between epigenetic states and mutational signature activities and allowed us to investigate the origins of SBS3, SBS5 and SBS40, focusing on the links to POL θ . The generation of point mutations by POL θ has been proposed to be related to its translesion synthesis activity during ssDNA gap filling [89, 78, 79], although other translesion polymerases may also play a role [91, 49, 92, 79]. The increased importance of POL θ in both replication-associated and DSB repair in cancer tumours coincides with the increase in replication stress caused by oncogenes [93].…”
Section: Discussionmentioning
confidence: 99%
“…51 Interestingly, SBS5 seems to be the signature that explains most of the intrinsic genetic variation in many different species. 61 SBS5 and SBS1 were also among the three most common signatures in another study in sperm where DS was used to sequence the FGFR3 gene coding region. 25 The proportions of the two signatures in sperm in our study (88% SBS5 and 12% SBS1) are also consistent with a study in seminiferous tubules 51 and a study on DNMs in more than 20,000 families 12 , both of which reported 85% of SBS5/40 and 15% of SBS1.…”
Section: Discussionmentioning
confidence: 95%
“…We note that SBS40, the most common SBS in the blood of our men, is highly similar to SBS5. 50,51 SBS40 (like SBS5 61 ) has an unknown etiology but is related to age. 50 If we combined SBS40 and SBS5 into a single signature, as previously done by others to account for their similarity, 51 then SBS5/40 and SBS1 were the most common signatures in both blood and sperm (Figure 6), with SBS5/40 being the most frequent.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses further confirm the importance of damage as a source not only of somatic mutations, but also for germline mutations [51, 58, 59]: over two-thirds of germline mutations are assigned to SBS1 and SBS5, signatures that arise from damage that is either not repaired or repaired incorrectly. The source of such DNA damage is most likely endogenous cellular processes, accounting for the omnipresence of these two signatures across cell types [2] and species [60], as well as their characteristic clock-like behavior under most conditions [42].…”
Section: Discussionmentioning
confidence: 99%